Hydraulic design of storm water infiltration facility including uncertainties - Duchan, David; Říha, Jaromír (Mendel University in Brno, 2016)
For a design of the volume of the rainfall infiltration facility, the coefficient of infiltration is determined by an infiltration test. The use of the coefficient of infiltration brings certain uncertainties into the solution, arising from different conditions in carrying out the infiltration test and in operating a real infiltration facility. In this study an analysis is carried out of factors that influence the process of infiltration and related uncertainties influencing the determination of the storage volume of the infiltration facility. The effect of the individual factors on the design of the infiltration facility was analyzed using numerical simulations by the software HYDRUS-2D and expressed using partial reliability factors. For their determination the nomographs were set up by extensive numerical computations.

For a design of the volume of the rainfall infiltration facility, the coefficient of infiltration is determined by an infiltration test. The use of the coefficient of infiltration brings certain uncertainties into the solution, arising from different conditions in carrying out the infiltration test and in operating a real infiltration facility. In this study an analysis is carried out of factors that influence the process of infiltration and related uncertainties influencing the determination of the storage volume of the infiltration facility. The effect of the individual factors on the design of the infiltration facility was analyzed using numerical simulations by the software HYDRUS-2D and expressed using partial reliability factors. For their determination the nomographs were set up by extensive numerical computations.
Hydraulic design of storm water infiltration facility including uncertainties
Keywords: infiltration facility; coefficient of infiltration; limit states; reability factors; infiltration facility; coefficient of infiltration; limit states; reability factors